General practitioners' perceptions on home medicines reviews: A qualitative analysis - Dhillon, A.; Hattingh, H. Laetitia; Stafford, A.; Hoti, Kreshnik (BioMed Central Ltd., 2015)
Background: Home Medicines Review (HMR) is an Australian initiative introduced in 2001 to improve quality use of medicines. Medication management services such as HMRs have the potential to reduce medication related problems. In 2011, changes to the HMR program were introduced to allow for referrals directly to accredited pharmacists in addition to the community pharmacy referral model. These changes were introduced to improve efficiency of the process. This study explored the perceptions of Western Australian general practitioners (GPs) on benefits and barriers of the HMR service and process, including their insights into the direct referral model. Methods: Purposive sampling of GPs who had experience ensured that participants had a working knowledge of the HMR service. Semi structured interviews with 24 GPs from 14 metropolitan Western Australian medical centres between March and May 2013. Transcribing and thematic analysis of data were performed. Results: Most GPs had positive attitudes towards the HMR service. Main perceived benefits of the service were poly-pharmacy reduction and education for both the GP and patient. Strategies identified to improve the service were introduction of a standard HMR report template for pharmacists and better use of technology. Whilst reliability and GPs' familiarity were the main perceived benefits of the direct referral model, a number of GPs agreed that patient unfamiliarity with the HMR pharmacist was a barrier. Conclusions: Despite recognition of the value of the HMR service participating GPs were of the opinion that there are aspects of the HMR service that could be improved. As one of the success factors of HMRs is relying on GPs to utilise this service, this study provides valuable insight into issues that need to be addressed to improve HMR uptake.